Co‐Based Bimetals: Enhanced Electrocatalytic Performance through Body Enrichment of Co‐Based Bimetallic Nanoparticles In Situ Embedded Porous N‐Doped Carbon Spheres (Small 44/2019). Issue 44 (29th October 2019) - Song, Qianqian; Li, Junqi; Wang, Shaolan; Liu, Junli; Liu, Xiaoxu; Pang, Lingyan; Li, Hu; Liu, Hui
Abstract : In article number 1903395, Junqi Li and co‐workers demonstrate how the enrichment and exposure of bimetallic nanoparticles in the body interior of porous carbon spheres, and the best balance between the adsorption of OH species and the desorption of O2 induced by the optimizing d‐band electrons, collectively enhance the oxygen evolution reaction performance.